PENGARUH PERCEIVED EASE OF USE TERHADAP INTENTION TO USE QRIS BCA MOBILE DENGAN PERCEIVED USEFULNESS SEBAGAI VARIABEL MEDIASI - Syahri , Anisah; Yanita Setyawati, Christina (Catholic University Musi Charitas, 2023)
Economic activity cannot be separated from the influence of technological and information development. One of the evidences of technological development in economic field is the availability of various cashless transaction pattern. Indonesian Bank and Indonesian Payment System Association launch QRIS is an integrated digital payment instrument. PT Bank Central Asia is one of the banking financial institution that offers QRIS service in BCA Mobile application. The convenience and benefit that are offered by QRIS BCA Mobile do not always run well. The purpose of this research is to look for the influence of between perceived ease of use on intention to use, perceived usefulness on intention to use, perceived ease of use on perceived usefulness, and perceived ease of use on intention to use through perceived usefulness as mediation variable. This research uses Structural Equation Modelling Partial Least Square (SEM PLS) data analysis method. Data in this research that is obtained by distributing questionnaires to 130 respondents of QRIS BCA Mobile users. The results of this research are there is influence between perceived ease of use on intention to use, perceived ease of use on perceived usefulness, perceived usefulness on intention to use, and perceived ease of use on intention to use with perceived usefulness as mediation variable.